Two tumors, one target: preliminary experience with 90Y-FAPI therapy in a patient with metastasized breast and colorectal cancer - Rathke, Hendrik; Fuxius, Stefan; Giesel, Frederik L.; Lindner, Thomas; Debus, Jürgen; Haberkorn, Uwe; Kratochwil, Clemens (Clinical nuclear medicine, 2021)
We report a patient with breast cancer (BC) diagnosed in 2009 with metachronous lymph node, liver, and bone metastases. In 2017, colorectal cancer with peritoneal metastases was additionally diagnosed and treated with 8 cycles of capecitabine due to its antitumor activity against both malignancies. At progression of both diseases, FAPI PET/CT demonstrated positive tumor targeting in BC-related metastases and colorectal cancer-related metastases. The patient received an experimental therapy with 90Y-FAPI46. Although there was similar tracer uptake in the PET/CT, the radioligand therapy resulted in mixed response with disappearance of peritoneal metastases but minor efficacy treating the BC-related metastases.
Im Titel ist "90" hochgestellt
Gesehen am 04.11.2021